Pengaruh Modal Usaha, Harga Jual, dan Lama Usaha Terhadap Pendapatan Pedagang Ayam Potong di Kecamatan Bati-Bati Kabupaten Tanah Laut - Vina; Khairi Pahlevi (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2026)
This study aims to analyze the influence of business capital, selling price, and business duration on the income of broiler chicken traders in Bati-Bati District, Tanah Laut Regency. The phenomenon of broiler chicken trading in this area is important to examine due to intense competition among traders and fluctuating market demand. This research used primary data collected from 37 respondents through a census method. Multiple linear regression analysis using EViews version 12 was applied to examine the simultaneous and partial effects of the independent variables on trader income. The findings indicate that business capital, selling price, and business duration simultaneously affect income. Partially, only business capital has a significant positive effect, while selling price and business duration are not statistically significant. Business capital is identified as the dominant determinant of income, indicating that greater capital enables traders to maintain stock availability and respond to demand more effectively. These findings imply that strengthening access to business capital may support income improvement among broiler chicken traders.